2004
DOI: 10.1002/ejlt.200300828
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid and 3‐hydroxy fatty acid composition of two Hypericum species from Turkey

Abstract: Fatty acid and 3-hydroxy fatty acid composition of two Hypericum species from TurkeyThe fatty acid compositions of flowering tops of Hypericum perforatum L. and Hypericum retusum Aucher (Guttiferae) were analyzed by gas chromatography and gas chromatography-mass spectrometry. The major components were C16:0 (24.87%), C18:3 n-3 (21.94%), 3-OH-C18:0 (18.46%) and 3-OH-C14:0 (14.22%) for H. perforatum L. and 3-OH-C14:0 (28.29%), C18:0 (16.47%) and C16:0 (14.17%) for H. retusum Aucher. Besides widespread plant fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The 3‐hydroxy fatty acids are an important class of microbial lipids that have been extensively used as biomarkers to aid microbial characterisation 35 . This class of compound is an unusual plant component, but the 3OH‐C18:0 was previously detected in leaves and flowers of some Hypericum species 36 . Besides 3OH‐C18:0, two other long chain fatty acids, C18:1 and C18:2, were identified only in rosemary leaf extracts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3‐hydroxy fatty acids are an important class of microbial lipids that have been extensively used as biomarkers to aid microbial characterisation 35 . This class of compound is an unusual plant component, but the 3OH‐C18:0 was previously detected in leaves and flowers of some Hypericum species 36 . Besides 3OH‐C18:0, two other long chain fatty acids, C18:1 and C18:2, were identified only in rosemary leaf extracts.…”
Section: Resultsmentioning
confidence: 99%
“…35 This class of compound is an unusual plant component, but the 3OH-C18:0 was previously detected in leaves and flowers of some Hypericum species. 36 Besides 3OH-C18:0, two other long chain fatty acids, C18:1 and C18:2, were identified only in rosemary leaf extracts. Previous authors have detected these compounds in the essential oil of rosemary leaves.…”
Section: Antioxidant Activitymentioning
confidence: 94%
“…Developing recombinant ALT enzymes with greatly increased 3-OH FA productivity could be achievable in the near future, as certain features of the ALT catalytic domain that can be manipulated to boost affinity for 3-OH fatty acyl-ACPs were uncovered in the present study. The capability of ALTs to act on 3-hydroxy-ACP intermediates of fatty acid biosynthesis could also prove useful in plant systems; however, while 3-hydroxy fatty acids are well-known components of bacterial endotoxins, they are rarely documented as plant metabolites outside of fatty acid biosynthesis, especially in the medium-chain length range [63][64][65]. It is unknown whether recombinant ALTs with preference for 3-hydroxyacyl-ACPs in E. coli would retain these preferences in planta.…”
Section: Alt Variants Have Unique Potential As Metabolic Engineering ...mentioning
confidence: 99%
“…Chapter 5: Summary of findings and future research directions While medium-chain fatty acids (FAs) and β-keto fatty acids (β-keto FAs) had been previously reported as products of Arabidopsis and wild tomato ALT enzymes, this work demonstrated that ALTs also generate medium-chain 3-hydroxy fatty acids (3-OH FAs). This is highly novel, as medium-chain 3-OH FAs had not been previously recorded as products of plant acyl-ACP thioesterases, and are rarely documented in plants outside of their role as intermediates in de novo fatty acid synthesis (Racovita et al, 2015;Clericuzio et al, 2017;Özen et al, 2004). As a result of ALT activity, many more plant species than presently known may produce medium-chain 3-OH FAs as secondary metabolites, with biological functions that are as of yet unexplored.…”
Section: -Conclusionmentioning
confidence: 95%
“…Developing recombinant ALT enzymes with greatly increased 3-OH FA productivity could be achievable in the near future, as certain features of the ALT catalytic domain that can be manipulated to boost affinity for 3-OH fatty acyl-ACPs were uncovered in the present study. The capability of ALTs to act on 3-hydroxy-ACP intermediates of fatty acid biosynthesis could also prove useful in plant systems; however, while 3-hydroxy fatty acids are well-known components of bacterial endotoxins, they are rarely documented as plant metabolites outside of fatty acid biosynthesis, especially in the mediumchain length range (Racovita et al, 2015;Clericuzio et al, 2017;Özen et al, 2004). It is unknown whether recombinant ALTs with preference for 3-hydroxyacyl-ACPs in E. coli would retain these preferences in planta.…”
Section: -Alt Variants Have Unique Potential As Metabolic Engineering...mentioning
confidence: 99%